آں حضورﷺ کے نادر نمونہ کلام"جوامع الکلم" میں محسنات لفظیہ کا مقام (Al-Qamar, 2020)
Man alone, among all creations, is bestowed with the quality of communication and conversation. Through the medium of communication, the personality, knowledge, competency and thinking level of a speaker can be explored. In the case of low communication skills, it remains impossible to change public opinion and appeal their attention towards a specific idea. All prophets of Allah Almighty were bestowed with the quality of magniloquent communication and eloquent speech. The last prophet Muhammad (P.B.U.H) was chosen among the persons who consider themselves most eloquent persons. They feel proud of their poets and orators. In this scenario, it was essential for the prophet (P.B.U.H) to have this ability of eloquence at the highest level. We find the expression of numerous and unique literary genres in the orations, addresses, sermons and discourses of Hazrat Muhammad (P.B.U.H). He (P.B.U.H) polished and refined by modification and alteration of former literary devices. His oratory and eloquence brought a revolution in the static literary lives of Arabs. In the modern era, in spite of majestic machinery and inventions, human communication efficiency is as important as was at the time of the pre-Islamic period. The demand of this era is to take help from the sublime examples of eloquent speech and literary genres of the Holy Prophet (P.B.U.H). This article will prove helpful for modern man to adopt the literary style of Hazrat Muhammad (P.B.U.H) and follow the preaching of Islam and also transform them to others.
Keywords: Communication; bestowed; magniloquent; eloquence; alteration; majestic; literary genres